Determination of the cleavage site of enterovirus 71 VP0 and the effect of this cleavage on viral infectivity and assembly. (September 2019) - Cao, Jiaming; Liu, Hongtao; Qu, Meng; Hou, Ali; Zhou, Yan; Sun, Bo; Cai, Linjun; Gao, Feng; Su, Weiheng; Jiang, Chunlai
Abstract: Hand, foot, and mouth disease (HFMD) is a major public health concern, especially among infants and young children. The primary pathogen of HFMD is enterovirus 71 (EV71), whose capsid assembly mechanism including capsid protein processing has been widely studied. However, some of its mechanisms remain unclear, such as the VP0 cleavage. This study aimed to identify the cleavage site of the EV71 VP0 capsid protein and to elucidate the effects of EV71 VP0 cleavage on viral infectivity and assembly. A mass spectrometry analysis indicated that the cleavage site of EV71 VP0 is located between residues Lys69 and Ser70. To analyze the importance of either residue to cleavage, we designed single mutations of Lys69, Ser70 and double mutations respectively and implemented these genomes to encapsulation. The results indicated that Ser70 is more important for VP0 cleavage and EV71 infectivity. In addition, exogenous expression of EV71 protease 2A and 3C was used to verify whether they play roles in VP0 cleavage. Analyses also showed that none of them participate in this process. This study provides novel insights into the mechanisms of EV71 capsid maturation, which may be a potential target to improve the productivity and immunogenicity of EV71 vaccines. Highlights: The EV71 VP0 cleavage site is located between Lys69 and Ser70. The serine70 residue at the VP0 cleavage site is more significant than the lysine69 residue for viral infectivity. EV71 2A and 3C proteases do not participate in VP0 cleavage.